Penyelesaian Perselisihan Pemutusan Hubungan Kerja yang Berkepastian Hukum terhadap Pekerja yang Melakukan Kesalahan Berat (Studi Kasus Putusan Nomor. 684/K/Pdt.SUS-PHI/2015) - Apriyanti, Luri; Horadin Saragih; Helvis; Anisa Fitria (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze the legal position of SEMA No. 3 of 2015 as a basis for termination of employment due to serious misconduct and to assess the application of the principle of legal certainty in resolving termination disputes based on Supreme Court Decision Number 684/K/Pdt.Sus-PHI/2015. The research employs a normative juridical method using statutory and conceptual approaches, as well as analysis of court decisions as jurisprudential legal sources. The findings indicate that the application of SEMA No. 3 of 2015 has the potential to weaken the principle of due process of law if serious misconduct is not proven through an adequate judicial mechanism. Therefore, the resolution of termination disputes must prioritize juridical proof as the primary instrument to ensure legal certainty and the protection of workers’ rights. The study concludes that the legal status of SEMA No. 3 of 2015 is limited as an internal judicial guideline and is not part of the hierarchy of laws and regulations under Law Number 12 of 2011; thus, it cannot override decisions of the Constitutional Court of Indonesia, which are final and binding. In cases of termination due to serious misconduct, legal certainty requires the employer to fully prove the grounds for dismissal; otherwise, the termination shall be declared unlawful. Keywords: Industrial Relations Dispute, Jurisprudence, Legal Certainty, Serious Misconduct, Termination of Employment.